Non-Cognitive Profiles in Medical Professionals: A Prisma-Guided Systematic Review (2020–2024) - Tjatur Ermitajani Judi (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Medical professionalism is grounded in ethical and humanitarian commitments; however, persistent ethical violations and malpractice cases indicate potential deficiencies in non-cognitive competencies. Despite growing scholarly attention, existing evidence remains fragmented and lacks comprehensive synthesis. Objective: This research systematically synthesizes empirical evidence (2020–2024) to identify appropriate and inappropriate non-cognitive profiles in medical professionals and to examine their implications for professionalism, clinical performance, and ethical conduct. Methods: This systematic review synthesizes empirical evidence identifying non-cognitive profiles supporting exemplary medical practice while distinguishing appropriate from inappropriate characteristics associated with ethical conduct and malpractice risk. Employing systematic methodology based on empirical literature (2020–2024), PRISMA 2020 guidelines ensured transparent evidence mapping, quality assessment, and synthesis across major databases (Scopus, Web of Science, PubMed) following standardized identification, screening, eligibility, and inclusion protocols. Results: Most included studies were observational and predominantly cross-sectional, with moderate methodological heterogeneity. Positive non-cognitive competencies—particularly empathy, resilience, emotional intelligence, professionalism, and compassion—demonstrate consistent associations with improved professional conduct, reduced burnout, and enhanced patient-related outcomes. In contrast, maladaptive traits, including Dark Triad characteristics, maladaptive perfectionism, and neuroticism, are associated with unethical behavior, interpersonal conflict, and diminished professional performance. Conclusion: Non-cognitive profiles constitute essential determinants of medical professionalism alongside cognitive competence. Although the evidence is largely observational, findings support the structured integration of non-cognitive assessment and development into medical education, professional selection, and continuing training frameworks to strengthen ethical standards and reduce professional misconduct.